Yes, There Will Be Singing - Krysl, Marilyn, 1942- (Book collections on Project MUSE., 2014)
This book brings together the author's essays on the origins of language and poetry, poetic form, the poetry of witness, and poetry's collaboration with the healing arts.--Publisher's description.